Phase Variation of LPS and Capsule Is Responsible for Stochastic Biofilm Formation in Francisella tularensis - Mlynek, Kevin D.; Lopez, Christopher T.; Fetterer, David P.; Williams, Janice A.; Bozue, Joel A. (Frontiers in Cellular and Infection Microbiology, 2022)
Biofilms have been established as an important lifestyle for bacteria in nature as these structured communities often enable survivability and persistence in a multitude of environments. Francisella tularensis is a facultative intracellular Gram-negative bacterium found throughout much of the northern hemisphere. However, biofilm formation remains understudied and poorly understood in F. tularensis as non-substantial biofilms are typically observed in vitro by the clinically relevant subspecies F. tularensis subsp. tularensis and F. tularensis subsp. holarctica (Type A and B, respectively). Herein, we report conditions under which robust biofilm development was observed in a stochastic, but reproducible manner in Type A and B isolates. The frequency at which biofilm was observed increased temporally and appeared switch-like as progeny from the initial biofilm quickly formed biofilm in a predictable manner regardless of time or propagation with fresh media. The Type B isolates used for this study were found to more readily switch on biofilm formation than Type A isolates. Additionally, pH was found to function as an environmental checkpoint for biofilm initiation independently of the heritable cellular switch. Multiple colony morphologies were observed in biofilm positive cultures leading to the identification of a particular subset of grey variants that constitutively produce biofilm. Further, we found that constitutive biofilm forming isolates delay the onset of a viable non-culturable state. In this study, we demonstrate that a robust biofilm can be developed by clinically relevant F. tularensis isolates, provide a mechanism for biofilm initiation and examine the potential role of biofilm formation.